U.S. monetary policy and emerging market credit cycles - Falk Bräuning; Victoria Ivashina (Federal Reserve Bank of Boston, 2017)
Foreign banks' lending to firms in emerging market economies (EMEs) is large and denominated primarily in U.S. dollars. This creates a direct connection between U.S. monetary policy and EME credit cycles. We estimate that over a typical U.S. monetary easing cycle, EME borrowers face a 32-percentage-point greater increase in the volume of loans issued by foreign banks than borrowers from developed markets face, with a similarly large effect upon reversal of the U.S. monetary policy stance. This result is robust across different geographical regions and industries, and holds for non-U.S. lenders, including those with little direct exposure to the U.S. economy. Local EME lenders do not offset the foreign bank capital flows; thus, U.S. monetary policy affects credit conditions for EME firms. We show that the spillover is stronger in higher-yielding and more financially open markets, and for firms with a higher reliance on foreign bank credit.
Keywords: E44; E52; F34; F44; G21; 330; Global business cycle; monetary policy; emerging markets; reaching for yield